(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Information andCommunication Technology (ICT) can be utilized for the education sector. Education includesonline, distance and part time education. There are unlimited applications ofICT in the real world. In his paper emphasis is on the education field.Traditional Non-formal education system process includes activities likeadmission, Personal Contact Programmes, Exam for any course in a University orInstitution. In this process ICT can play a great role in all the activities byproviding a lot of benefits to students, teachers, parents and Universitiesitself. ICT can be used for providing education to the people who are not ableto come to school due to various constraints. ICT can play great role in formaland non-formal forms of education. The paper examines certain important issuesrelated with the effective implementation of ICTs in all levels of educationand provides suggestions to address certain challenges that would help in theimplementation of ICTs in education and simultaneously increasing Quality ofeducation.